INFLUENCE OF METABOLIC PARAMETERS ON LDL AND HDL SIZE AND SUBCLASSES IN ADOLESCENTS WITH TYPE 1 DIABETES: LIPOPROTEIN FRACTIONS IN ADOLESCENTS WITH DIABETES TYPE 1 - Kovačević, Smiljka; Zdravković, Vera; Đorđević, Stefan; Ješić, Miloš M; Zeljković, Aleksandra; Dejana Stanisavljević; Vuković, Milica; Ješić, Maja D (Medical Research, 2022)
Introduction Alterations in serum of low-density lipoprotein (LDL) and high-density lipoprotein (HDL) size and subclasses contribute to the atherogenesis in coronary artery disease in diabetic patients. Aim The purpose of this study is to evaluate the effect of metabolic parameters on LDL and HDL size and subclasses in adolescents with type 1 diabetes. Methods The cross-sectional study included 43 adolescents (23 females, 20 males) with type 1 diabetes of mean age 15.09±1.94 years, with mean disease duration of 5.86 ± 3.08 years. LDL and HDL particles were separated by polyacrylamide gradient gel electrophoresis, while serum lipid parameters were determined by routine laboratory methods. Results Patients with inadequate metabolic control (HbA1c ≥ 7.5%) had a higher mean value of triglycerides (TG) (p = 0.041), higher proportions of small, dense LDL particles (p = 0.045), higher proportions of LDL IIA subclasses (p=0.03) and smaller LDL diameter (p = 0.02) and HDL diameter (p = 0.04) than patients with optimal metabolic control (HbA1c < 7.5%). Higher HbA1c and higher TG levels were statistically significantly related to small, dense LDL (ρ=0.341, p=0.025; ρ= 0.394, p= 0.009) and HDL particles (ρ=0.684, p=0.000; ρ=0.421, p=0.005). Predictors of small, dense LDL and HDL particles, which contribute to atherogenesis, were high HbA1c (HR = 1.52, 95% CI: 0.97-2.40; HR 3.87, 95% CI: 2.11-7.10) and elevated TG (HR= 1.10, 95% CI: 1.00-1.20; HR 1.85, 95% CI: 1.07-3.21). Conclusion Diabetic adolescents require particular attention in order to minimize factors such as high HbA1c and elevated TGs in the development of future cardiovascular events.